2005
DOI: 10.1529/biophysj.104.043976
|View full text |Cite
|
Sign up to set email alerts
|

Calcium Mobilization and Spontaneous Transient Outward Current Characteristics upon Agonist Activation of P2Y2 Receptors in Smooth Muscle Cells

Abstract: A quantitative model is provided that links the process of metabotropic receptor activation and sequestration to the generation of inositol 1,4,5-trisphosphate, the subsequent release of calcium from the central sarcoplasmic reticulum, and the consequent release of calcium from subsarcolemma sarcoplasmic reticulum that acts on large-conductance potassium channels to generate spontaneous transient outward currents (STOCs). This model is applied to the case of STOC generation in vascular A7r5 smooth muscle cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 65 publications
(84 reference statements)
0
10
0
Order By: Relevance
“…We showed that both agonists act via two P2Y subtypes to evoke contraction in this tissue, most likely P2Y 6 , plus P2Y 2 or P2Y 4 receptors (Chootip et al ., 2002; 2005; Kennedy et al ., 2010). P2Y 2 (Sromek and Harden, 1998; Flores et al ., 2005; Lemon et al ., 2005) and P2Y 4 (Brinson and Harden, 2001) receptors both desensitize rapidly and with a time‐course compatible with the decay seen in the present study, whereas the P2Y 6 receptor desensitizes much more slowly, reaching a steady‐state over 3–6 h (Robaye et al ., 1997; Brinson and Harden, 2001). Thus, the activation of P2Y 6 and P2Y 2 /P2Y 4 receptors could together lead to the peak contraction, with the subsequent decay reflecting desensitization of P2Y 2 /P2Y 4 receptors, to leave P2Y 6 receptors dominating the plateau.…”
Section: Discussionmentioning
confidence: 99%
“…We showed that both agonists act via two P2Y subtypes to evoke contraction in this tissue, most likely P2Y 6 , plus P2Y 2 or P2Y 4 receptors (Chootip et al ., 2002; 2005; Kennedy et al ., 2010). P2Y 2 (Sromek and Harden, 1998; Flores et al ., 2005; Lemon et al ., 2005) and P2Y 4 (Brinson and Harden, 2001) receptors both desensitize rapidly and with a time‐course compatible with the decay seen in the present study, whereas the P2Y 6 receptor desensitizes much more slowly, reaching a steady‐state over 3–6 h (Robaye et al ., 1997; Brinson and Harden, 2001). Thus, the activation of P2Y 6 and P2Y 2 /P2Y 4 receptors could together lead to the peak contraction, with the subsequent decay reflecting desensitization of P2Y 2 /P2Y 4 receptors, to leave P2Y 6 receptors dominating the plateau.…”
Section: Discussionmentioning
confidence: 99%
“…Calcium levels can vary substantially from one cell type to another. For example, in excitable cells such as neuronal cells and muscle cells, for which most calcium models and measurement techniques have been developed (13,21,(24)(25)(26)(27)(28), basal [Ca 21 ] i is in the 0.2-0.5 mM range, whereas in nonexcitable cells such as macrophages, including RAW 264.7 cells (29,30), it is between 0.03 and 0.1 mM. In macrophages, due to their nonexcitable nature, oscillations are generally not observed, as evidenced by the Alliance for Cellular Signaling (AfCS) calcium data (29) and discussed in (30)(31)(32).…”
Section: Variation Across Different Cell Typesmentioning
confidence: 99%
“…SMCs of various types have been studied extensively. A number of models describing various physiological features of SMC related to cellular Ca 2þ dynamics have been presented in the literature (35)(36)(37)(38)(39). These models, although relevant to their respective cell types, are not directly applicable to ASMCs due to differences in physiological structure and function.…”
Section: Discussionmentioning
confidence: 99%